Recognition and criticism in modern leadership - A study on the usage of recognition, appreciation and criticism as instruments of leadership - Stephanie Göll; Philipp Rettler (Journal für Psychologie, 2011)
Recognition and appreciation are key drivers for motivation and are able to affect the success of the company. Appreciative communication is therefore essential for successful leadership. Appreciation as well as criticism are indispensable instruments for all managerial functions. Leadership principals and the idea of man shape the behavior of any manager and define his/her style of appreciating and criticising and the preferred instruments: Depending on the managerial style of the supervisor, he/she forms his/her understanding how appreciation and review should be articulated. Despite the growing importance of appreciation, recognition and criticism for leadership and the increasingly sophisticated approach, just few studies have been carried out so far concerning this topic. The aim of the study "Successful leadership through appreciation - Recognition and appreciation as motivational instruments of modern personnel management" which was carried out in 2008 was to clarify the relationship of management styles and appreciation. The main hypothesis of this study assumed a correlation of leadership styles and the different forms of appreciation and criticism. Furthermore it was presumed that leadership styles are defined through the situational context and not through personal characteristics of the manager. Both assumptions were confirmed through the study. The results show, that appreciation and review are important leadership instruments and implicate a sensible handling to ensure the development of achievement potential of every employee.